Chronic exposure to environmentally relevant diazepam alters behaviour, gut microbiome, and offspring phenotype in zebrafish (Danio rerio) - Ting Xu; Yilin Huang; Guiling Yang; Wenqin Tu; Ting Luo; Dou Wang; Yuanxiang Jin (Environmental Pollution, 2026)

Lithium enrichment in geothermal systems of the Tibetan Plateau: A coupled machine learning–geochemistry framework for mechanism and prediction - Shuaichao Wei; Wei Zhang; Guiling Wang; Feng Liu; Feng Tian; Xiaoxue Yan; Ruoxi Yuan; Zengrun Yang; Yong Fu (Earth-Science Reviews, 2026)

Unveiling the dominant role of LiOH in interfacial degradation: A quantitative strategy for tailored surface coating on Ni-rich cathodes - Fushui Zhou; Ruijie Wang; Wenhui Wang; Yuxuan Zhang; Guiling Yang (Chemical Engineering Journal, 2026)

Transcriptomics analysis elucidates the growth inhibitory mechanisms of volatile fungistatic compound 3-ethylbenzaldehyde to Pseudocryphonectria elaeocarpicola - Yuchen Yang; Guiling Ran; Haoyu Wu; Liangji Li; Dianguang Xiong; Huayi Huang; Chengming Tian (Pesticide Biochemistry and Physiology, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Polyethylene microplastics differently induced gut microbiota dysbiosis and hepatic metabolism in male and female adult zebrafish - Zhiwei Bao; Ting Luo; Yao Zhao; Guiling Yang; Yuanxiang Jin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Returning straw and applying appropriate nitrogen fertilizer could increase acid-hydrolysable ammonium nitrogen and amino sugar nitrogen in the soil, thereby promoting effective panicle number and ultimately boosting rice yield - Linya Lu; Zhengli Song; Yang Hu; Liang Luo; Guiling Xu; Yuehua Feng; Muhammad Usama Latif; Somsana Phonenasay; Bingping Cui; Xiangjun Xu; Jianhua Huang; Yanni Wei (Plant and Soil, 2026)

Ultrasensitive and selective detection of metronidazole residues in milk powder using a novel 3D MOF fluorescent sensor - Xuanqi Zhang; Guiling Gao; Xiaoyong Lai; Qin Hou; Yi Li; Zhiyong Teng; Xiaozhong Wang; Xiao Zhang; Qingfeng Yang (Food Chemistry, 2026)

Baculovirus manipulation of nutrient-based host choice via an infection responsive olfactory receptor in Spodoptera exigua - Zaiyuan Li; Xin Gao; Qihong Ma; Lianhai Fu; Changyou Li; Yan Shi; Jie Li; Qianlong Yu; Guiling Zheng; Chunhong Yang; Fanghao Wan; Wanqiang Qian; et al. (Pesticide Biochemistry and Physiology, 2026)

Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Global immunostimulatory mechanisms of a high-branched glycogen from Glyptocidaris crenularis eggs in RAW264.7 macrophages via BONCAT-based nascent proteomics - Qingchi Wang; Yuhang Luo; Yi Xin; Yuanxiang Jin; Guiling Yang; Quanbin Zhang; Zhengshun Wen (Carbohydrate Polymers, 2025)

A SERS-active microneedle array for rapid and minimally invasive lactic acid detection - Xinyu Sun; Kequan Chen; Yang Wang; Zhiwei Zhang; Jinfeng Lin; Guiling Liu; Dianhuai Meng; Jian Dong; Yan Huang (Analytica Chimica Acta, 2025)

The physiological effects of intrinsic and isolated arabinoxylans on human immunometabolic response: A systematic review and meta-analysis - Shanshan Jiang; Chenxi Cai; Edward C. Deehan; Junyu Chen; Changcan Feng; Mingyue Yang; Zhongming Weng; Jiahui Long; Jiaxuan Xie; Shan Lin; Guiling Li; Jian Li; et al. (Food Research International, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

Plant-derived exosome-like nanoparticles – from Laboratory to factory, a landscape of application, challenges and prospects - Chaozhi Wei; Mengyu Zhang; Jintao Cheng; Jinzhong Tian; Guiling Yang; Yuanxiang Jin (Critical Reviews in Food Science and Nutrition, 2025)

Petrological and geochemical insights into the genesis and geothermal potential of Late Neoarchean granitoid rocks in the Matouying Uplift, North China Craton - Quan Gan; Luming Song; Shuantong Shangguan; Xiaofei Qi; Zhiwei Liao; Jianye Chen; Zhili Yang; Guiling Wang; Guangyao Xin; Chongyuan Zhang (Precambrian Research, 2025)

Genetically engineered Bacillus subtilis-derived extracellular vesicles Alleviates Ulcerative colitis by restoring intestinal barrier and regulating gut microbiota - Jiali Chen; Chaozhi Wei; Chunqiang Pan; You Wei; Baoxian Li; Tao Liu; Xiao Wang; Zhengshun Wen; Yao Zhao; Mengyu Zhang; Jintao Cheng; Yuanxiang Jin; et al. (Chemical Engineering Journal, 2025)

Evaluating the effects of intrinsic and isolated arabinoxylans on human gut microbiota and short-chain fatty acids: A systematic review and meta-analysis - Changcan Feng; Chenxi Cai; Edward C. Deehan; Shanshan Jiang; Mingyue Yang; Zhongming Weng; Jiahui Long; Guiling Li; Jian Li; Jingwen Liu; Zhengxiao Zhang (Trends in Food Science & Technology, 2025)

Regulation and response of heterotrophic bacterial production to environmental changes in marginal seas of the Western Pacific Ocean - Qiao Liu; Jinyan Wang; Xiao-Jun Li; Ni Meng; Gui-Peng Yang; Guiling Zhang; Guang-Chao Zhuang (Global and Planetary Change, 2025)

Refining water and carbon fluxes modeling in terrestrial ecosystems via plant hydraulics integration - Shanshan Sun; Lingcheng Li; Zong-Liang Yang; Guiling Wang; Nate G. McDowell; Ashley M. Matheny; Jian Wu; Shiqin Xu; Hui Zheng; Miao Yu; Dagang Wang (Agricultural and Forest Meteorology, 2024)

Exploring the dynamic behaviors of five pesticides in lettuce: Implications for consumer health through field and modeling experiments - Yanhua Wang; Panpan Liu; Guiling Yang; Fang Shu; Chen Chen (Food Chemistry, 2024)

Spatiotemporal modulation of immune microenvironment via composite hydrogel brakes for diabetic wound healing - Jiaying Yang; Mengyu Lai; Yuhang Ma; Jingzhu Wu; Chuan Zhang; Huiwen Yuan; Guiling Liang; Chuchen Meng; Yanmei Su; Bing Luan; Liping Gu; Yufan Wang (Chemical Engineering Journal, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Antibiotic resistance gene distribution in Shine Muscat grapes and health risk assessment of streptomycin residues in mice - Weitao Wang; Ting Luo; Yao Zhao; Xinyuan Yang; Dou Wang; Guiling Yang; Yuanxiang Jin (Journal of Hazardous Materials, 2024)

A review of cumulative risk assessment of multiple pesticide residues in food: Current status, approaches and future perspectives - Mengxue Yang; Yihan Wang; Guiling Yang; Yanhua Wang; Fengquan Liu; Chen Chen (Trends in Food Science & Technology, 2024)

The occurrence of typical psychotropic drugs in the aquatic environments and their potential toxicity to aquatic organisms - A review - Xianghai Zhu; Ting Luo; Dou Wang; Yao Zhao; Yuanxiang Jin; Guiling Yang (Science of The Total Environment, 2023)

Nano- and micro-polystyrene plastics interfered the gut barrier function mediated by exosomal miRNAs in rats - Zhuizui Huang; You Weng; Qichen Shen; Yao Zhao; Ting Luo; Yingping Xiao; Guiling Yang; Yuanxiang Jin (Environmental Pollution, 2023)

Study on the Role of Mitophagy Receptor PHB2 in Doubly Uniparental Inheritance of Hyriopsis cumingii - Yayu Wang; Xiaoyue Zhu; Yang Gu; Zongyu Liu; Yingrui Mao; Xiaojun Liu; Zhiyi Bai; Guiling Wang; Jiale Li (Marine Biotechnology, 2023)

Heat stress to jeopardize crop production in the US Corn Belt based on downscaled CMIP5 projections - Meijian Yang; Guiling Wang (Agricultural Systems, 2023)

Associations between environmental heavy metals exposure and preserved ratio impaired spirometry in the U.S. adults - Chen Chen; Shunan Zhang; Ting Yang; Chen Wang; Guiling Han (Environmental Science and Pollution Research, 2023)
We examined 9556 individuals aged 18 to 79 years who had information on spirometry testing and heavy metals and used multivariable logistic or linear regression to evaluate associations between serum levels of cadmium, lead, and mercury and PRISm and lung function in U.S. adults, which were conducted first in all participants, and then separately in never/former smokers and current smokers. The overall prevalence of PRISm was 7.02%. High levels of serum cadmium were significantly associated with PRISm in all individuals, no matter in never/former smokers (quartile 4 vs 1, the OR = 2.517, 95% CI = 1.376–4.604, p -trend = 0.0077) and current smokers (quartile 4 vs 1, the OR = 2.201, 95% CI = 1.265–3.830, p -trend = 0.0020). Serum lead and mercury were not significantly correlated with PRISm, regardless of smoking status. Serum cadmium was strongly correlated with lower FEV 1 /FVC, regardless of smoking status. Besides, serum cadmium was also significantly related to lower FVC % predicted in never/former smokers and lower FEV 1 % predicted in current smokers. Serum lead was strongly correlated with lower FVC % predicted and FEV 1 /FVC in all individuals and never/former smokers. And serum mercury was significantly associated with decrements in FVC % predicted in all individuals and current smokers. These findings demonstrate that serum cadmium is associated with a higher risk of PRISm and lower lung function, with the most significant effect on FEV 1 /FVC in particular. Our results also indicate that exposure to lead and mercury negatively affects lung function in never/former smokers and current smokers, respectively.

Water stress dominates the projected maize yield changes in Ethiopia - Meijian Yang; Guiling Wang; Ying Sun; Liangzhi You; Richard Anyah (Global and Planetary Change, 2023)

A Responsive Feeding Questionnaire Based on Self-Determination Theory for Caregivers of Chinese Toddlers - Yan Liu; Guiling Yu; Zhihui Li; Yan Kong; Rui Yang; Chunlan Yin; Xiaodi Sun (Journal of Nutrition Education and Behavior, 2023)

Seasonal prediction of crop yields in Ethiopia using an analog approach - Meijian Yang; Guiling Wang; Shu Wu; Paul Block; Rehenuma Lazin; Sarah Alexander; Jonathan Lala; Muhammad Rezaul Haider; Zoi Dokou; Ezana Amdework Atsbeha; Marika Koukoula; Xinyi Shen; et al. (Agricultural and Forest Meteorology, 2023)

Joint toxic effects of thiamethoxam and flusilazole on the adult worker honey bees (Apis mellifera L.) - Dou Wang; Lu Lv; Zhongwen Gao; Yu-Cheng Zhu; Hongbiao Weng; Guiling Yang; Yanhua Wang (Environmental Pollution, 2023)

Benthic nitrogen cycling in the deep ocean of the Kuroshio Extension region - Haoming Xu; Guodong Song; Siqi Yang; Ruosi Zhu; Guiling Zhang; Sumei Liu (Frontiers in Marine Science, 2022)
Benthic nitrogen cycling, including nitrification, N-loss, and other nitrogen transformations, plays a crucial role in the marine nitrogen budget. However, studies on benthic nitrogen cycling mainly focus on marginal seas, while attention to the deep ocean, which occupies the largest area of the seafloor, is severely lacking. In this study, we investigate the benthic nitrogen cycling in the Kuroshio Extension region (KE) of the northwest Pacific Ocean at water depths greater than 5,000 m through 15 N enrichment slurry incubation and pore-water dissolved oxygen and inorganic nitrogen profiles. The slurry incubation indicates nitrification is the predominant process in benthic nitrogen cycling. The potential nitrification rates are nearly an order of magnitude higher than dissimilatory nitrate reduction. Nitrification and total N-loss flux estimated from pore-water nitrate and ammonium profiles are 6–42 and 5–30 μmol N m −2 d −1 , respectively. Generally, anammox is the predominant N-loss process in KE sediment. The temperature gradient experiment indicates that the optimum temperature for anammox and denitrification is 13 and 41°C, respectively, partially explaining anammox as the dominant process for deep-ocean benthic N-loss. Both the low concentration of ammonium in pore-water and the discrepant results between anoxic incubation amended with 15 NO 3 − and 15 NH 4 + + 14 NO 3 − suggest that ammonium is another limiting factor for benthic anammox. N-loss activity gradually declines with the distance from the Oyashio–Kuroshio transition zone. However, nitrification has the opposite trend roughly. This reveals that the sediment in KE transfers from nitrate sink to source from north to south. This trend is mainly caused by the variation of primary production and the supplement of active organic matter, which is the energy source for microbes and the potential source for ammonium through remineralization. Overall, our results highlight temperature and ammonium as two limiting factors for deep-ocean benthic N-loss and also exhibit a tight coupling relationship between pelagic primary production and the benthic nitrogen cycle in KE.

G-CSF promotes the viability and angiogenesis of injured liver via direct effects on the liver cells - Zifeng Liu; Guiling Zhang; Jing Chen; Jingjing Tong; Hongmin Wang; Jing Chen; Dong Yang; Jinhua Hu (Molecular Biology Reports, 2022)
Background Presently, liver transplantation is the only treatment strategy for liver failure (LF). Although granulocyte-colony stimulating factor (G-CSF) exhibits protective functions in LF, it is not clear whether it directly affects the liver cells. Methods and Results We established an injured liver cell model and observed that G-CSF treatment promoted cell viability and enhanced Ki67 and VEGF-A expression. Thereafter, human umbilical vein endothelial cells (HUVECs) were cultured in a conditioned medium collected from the G-CSF-treated injured liver cells. HUVECs’ proliferation and tubule formation were promoted. Furthermore, in an injured liver mouse model, confirmed via haematoxylin–eosin staining, we evaluated serum alanine aminotransferase activity, Ki67 expression, and microvessel density (MVD). G-CSF treatment significantly relieved liver injury, upregulated Ki67 expression, and enhanced MVD in the injured mouse liver tissue. Additionally, AKT and ERK signal targets were explored, and it was demonstrated that the effects of G-CSF on injured liver cells were mediated through the AKT and ERK signalling pathways. Conclusions G-CSF promotes injured liver viability and angiogenesis by directly affecting injured liver cells via the AKT and ERK signalling pathways. These findings improve our understanding of the role of G-CSF in recovery from LF.

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Combined toxic impacts of thiamethoxam and four pesticides on the rare minnow (Gobiocypris rarus) - Guiling Yang; Lu Lv; Shanshan Di; Xinfang Li; Hongbiao Weng; Xinquan Wang; Yanhua Wang (Environmental Science and Pollution Research, 2021)

Toxicological interactions of cadmium and four pesticides on early life stage of rare minnow (Gobiocypris rarus) - Yanhua Wang; Xinfang Li; Chao Xu; Guiling Yang; Dou Wang; Xinquan Wang; Qiang Wang (Ecotoxicology, 2020)

Projecting the future vegetation–climate system over East Asia and its RCP-dependence - Weiguang Liu; Guiling Wang; Miao Yu; Haishan Chen; Yelin Jiang; Meijian Yang; Ying Shi (Climate Dynamics, 2020)

Three Types of Spatial Function Zoning in Key Ecological Function Areas Based on Ecological and Economic Coordinated Development: A Case Study of Tacheng Basin, China - Guiling Wang; Degang Yang; Fuqiang Xia; Ruisen Zhong; Chuanhe Xiong (Chinese Geographical Science, 2019)

Identification of porcine CTLA4 gene polymorphism and their association with piglet diarrhea and performance traits - Xiaowen Gao; Dongchun Guo; Mingxing Kou; Guiling Xing; Andong Zha; Xiuqin Yang; Xibiao Wang; Shengwei Di; Jiancheng Cai; Buyue Niu (Molecular Biology Reports, 2019)

The dissipation and risk assessment of 2,4-D sodium, a preharvest anti-fruit-drop plant hormone in bayberries - Huiyu Zhao; Guiling Yang; Senmiao Liang; Qianbin Huang; Qiang Wang; Wanze Dai; Zhiheng Zhang; Wen Wang; Wen Song; Zheng Cai (Environmental Science and Pollution Research, 2017)

Combined toxicity of imidacloprid and three insecticides to the earthworm, Eisenia fetida (Annelida, Oligochaeta) - Tao Cang; Dejiang Dai; Guiling Yang; Yijun Yu; Lu Lv; Leiming Cai; Qiang Wang; Yanhua Wang (Environmental Science and Pollution Research, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Individual and mixture effects of five agricultural pesticides on zebrafish (Danio rerio) larvae - Yanhua Wang; Guiling Yang; Dejiang Dai; Zhenlan Xu; Leiming Cai; Qiang Wang; Yijun Yu (Environmental Science and Pollution Research, 2017)

Identification and characterization of a novel NAC-like gene in chrysanthemum (Dendranthema lavandulifolium) - Yanfang Yang; Kai Zhu; Jian Wu; Liqing Liu; Guiling Sun; Yanbiao He; Fadi Chen; Deyue Yu (Plant Cell Reports, 2016)

SIRT1 activation by pterostilbene attenuates the skeletal muscle oxidative stress injury and mitochondrial dysfunction induced by ischemia reperfusion injury - Yedong Cheng; Shouyin Di; Chongxi Fan; Liping Cai; Chao Gao; Peng Jiang; Wei Hu; Zhiqiang Ma; Shuai Jiang; Yushu Dong; Tian Li; Guiling Wu; et al. (Apoptosis, 2016)

HO-1 Signaling Activation by Pterostilbene Treatment Attenuates Mitochondrial Oxidative Damage Induced by Cerebral Ischemia Reperfusion Injury - Yang Yang; Jiayi Wang; Yue Li; Chongxi Fan; Shuai Jiang; Lei Zhao; Shouyin Di; Zhenlong Xin; Bodong Wang; Guiling Wu; Xia Li; Zhiqing Li; et al. (Molecular Neurobiology, 2016)

Activation of endoplasmic reticulum stress is involved in the activity of icariin against human lung adenocarcinoma cells - Shouyin Di; Chongxi Fan; Yang Yang; Shuai Jiang; Miaomiao Liang; Guiling Wu; Bodong Wang; Zhenlong Xin; Wei Hu; Yifang Zhu; Weimiao Li; Yongan Zhou; et al. (Apoptosis, 2015)

Joint toxicity of chlorpyrifos, atrazine, and cadmium at lethal concentrations to the earthworm Eisenia fetida - Guiling Yang; Chen Chen; Yanhua Wang; Leiming Cai; Xiangzhen Kong; Yongzhong Qian; Qiang Wang (Environmental Science and Pollution Research, 2015)

Impact of climate change on hydrological extremes in the Yangtze River Basin, China - Huanghe Gu; Zhongbo Yu; Guiling Wang; Jigan Wang; Qin Ju; Chuanguo Yang; Chuanhao Fan (Stochastic Environmental Research and Risk Assessment, 2015)

Health risk assessment of Chinese consumers to nickel via dietary intake of foodstuffs - Wen Wang; Zhiheng Zhang; Guiling Yang; Qiang Wang (Food Additives & Contaminants: Part A, 2014)

Polycyclic aromatic hydrocarbons in urban soils of Hangzhou: status, distribution, sources, and potential risk - Guoguang Yu; Zhiheng Zhang; Guiling Yang; Weiran Zheng; Lihong Xu; Zheng Cai (Environmental Monitoring and Assessment, 2014)

Identification of QTLs for salt tolerance at germination and seedling stage of Sorghum bicolor L. Moench - Hailian Wang; Guiling Chen; Huawen Zhang; Bin Liu; Yanbing Yang; Ling Qin; Erying Chen; Yanan Guan (Euphytica, 2014)

ITS sequence-based identification and utilization evaluation of “Nanjiang” (Lonicera similis Hemsl.), a local cultivar in Sichuan, China - Shangqin Hu; Guiling Dong; Xiaomin Chen; Lulin Huang; Xiao Yang; Wen Tong; Linhan Bai (Genetic Resources and Crop Evolution, 2012)